Vision-related tasks in children with visual impairment: a multi-method study - Ghasemi Fard, Fatemeh; Mirzaie, Hooshang; Hosseini, Seyed Ali; Riazi, Abbas; Ebadi, Abbas (Frontiers in Psychology, 2023)
Objective: Functional Vision (FV) is vital for the successful growth of children with visual impairment. However, tasks related to measuring FV have not been thoroughly studied for this population. To address this gap, this study seeks to establish a comprehensive set of vision-related tasks that consider both the difficulty levels of activities and the ages of children with visual impairment. Methods: This study utilized a sequential multi-method design, including a scoping review, a qualitative content analysis, and a focus group. Firstly, a scoping review was conducted to identify vision-related tasks based on the literature. Then, to contextualize the vision-related tasks, a qualitative content analysis was carried out. Subsequently, a focus group was conducted to categorize the identified tasks based on their difficulty levels and the children's level of dependency. We utilized the directed content analysis method to analyze the data, using the occupational domain of the Occupational Therapy Practice Framework 4th edition (OTPF-4) as the primary framework. Results: During the review phase, which included 22 studies, and the interview phase, which involved 16 participants, a total of 95 and 85 vision-related tasks were identified, respectively. These tasks were then categorized into 17 activities and five occupations, which included activities of daily living (ADL), instrumental activities of daily living (IADL), education, play, and participation in social activities. Among these occupations, ADL was the easiest, while participation in social activities was the most challenging. Finally, the tasks were arranged based on their difficulty level for children with visual impairment. Conclusion: A comprehensive list of vision-related tasks has been developed based on the difficulty level of the tasks and the degree of dependency of children with visual impairment. This list can be used to develop standardized instruments for assessing FV in children with visual impairment. Keywords: Children with visual impairment, Vision-related tasks, OTPF-4, Occupational therapy